POTRET PERJUANGAN TOKOH PEREMPUAN IDAH DALAM CERPEN PEREMPUAN PEREMPUAN PERAWAT KENANGAN - Azqi Zakiatal Fitri (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2020)
The short stories of women - women nurses memories are short stories by Tiara Sari which were published early in the 17 January 2016 edition of Haluan Padang, then recorded in the first printed collection of short stories of women - women nurses in 2019. a creature that is complicated and difficult to understand, making it difficult to understand what is in his heart and what he wants. But the woman tried to get up in her own way so as not to get worse.So in this case, the writer appointed a female character named